Thermal imaging of a vein in the forearm: any correlation to blood pressure? - Tan, Wei Long (2016)
Blood pressure is one of the most important measurements for the human health. The main reason for the need to monitor blood pressure regularly is to prevent cardiovascular diseases. Currently, the most common equipment used to measuring blood pressure is a sphygmomanometer. This measurement tool will provide the values of the systolic and diastolic pressures of the human body. However, this method causes much discomfort to the person measuring his/her blood pressure due to expanding of the cuffs. Previous researchers have tried to use the technique of thermal imaging and processing to study blood flow and pressure. This technique would be possible, however, the cost of equipment (thermal camera and processer) is far too expensive. This project was carried out in hopes to find a non-invasive method of measuring superficial temperature using a contactless thermal sensing thermometer and thermocouples, correlating temperature with blood velocity. Finally to obtain blood pressure readings from correlating to blood velocity. In order to achieve this objective, previous methods of using thermal imaging were studied in order to look for similarities. A mathematical model was derived based on previous work by previous researchers. Then after, simulations were carried out using COMSOL Multiphysics with a simplified model of the human forearm. Experiments were carried out to firstly verify the results of the simulations of superficial skin temperature. Further experiments were done with the aim of obtaining fluid velocity and pressure by using correlations of superficial temperature.